Estimation Hazard of Lung Cancer Due to Radiate Radon Gas in Diyala Governorate Schools - Jassem Kadhim, Mothana; Ahmed Ebrahiem, Sameera (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
In this research, the concentration of radon gas has been calculated in the classrooms of schools in Diyala Governorate by using the nuclear track detector (CR-39), which was one of the organic solid-state nuclear detectors (SSNTDs). After calculating the radon gas concentration, the lung cancer cases were calculated. The results showed that the lowest value was found in (Alshumue) school (4.753) people. In contrast, the highest value was found in (Habhib) school (20.421). The average values of lung cancer cases in Diyala governorate were equal to (9.319) per person. The results showed that the number of lung cancer cases per year per million persons in Diyala Governorate schools was below the allowed limit from (ICRP) agency (170-230) people.